Sự tương tác lẫn nhau giữa các ion chuyển tiếp trong các xúc tác phức hỗn hợp (Me2++Me2+)En - Minh Nguyệt, Trần Thị; Xuyến, Nguyễn Văn (Vietnam Journal of Chemistry, 2014)
he kinetics of reaction in the H2O-(Me+Me’)Eni-H3BO3-H2O2-Ind systems were determined, where Me, Me’ = Mn2+, Fe2+, Co2+, Ni2+, Cu2+, En-ethylenediamine, Ind-indigocarmine. The obtained data show an interaction between manganese and iron  in the mixed system of Mn2+Eniand Fe2+Eni. This effect makes a raise of the reaction rate of mixed system. Oppositely, ions Cu2+,Ni2+, Co2+ cause a negative effect for catalytic activity of the mixed systems with Mn2+Enior Fe2+Eni; however in its mixed systems (such as Cu2++Ni2+, Cu2++Co2+, Ni2++Co2+ with En) there is feeble positive effect